INSTITUTIONAL ENVIRONMENT AND THE DEVELOPMENT OF FRANCHISE CHAINS IN THE NORTHERN REGION OF BRAZIL (Gestão & Regionalidade, 2024)
The objective of this study is to identify which dimensions of the institutional environment are related to the presence of franchise chains in the Northern Region of Brazil. To achieve this objective, we used data from the ABF, of the 129 cities in the region, and data of the institutional environment, from the IBGE. The measurement of statistical data was performed using the technique of multiple regression and multivariate analysis. The results confirmed the three hypotheses of the study, and it is possible to conclude that the better the indicators related to demography, economic and human resources, the greater the attractiveness of franchise chains. It is hoped to contribute to the enrichment of the theory of the institutional environment, aimed at business expansion, and to the diffusion of the theory of geographic expansion to the Northern Region of Brazil, focusing on the model of franchise chains.